Intramuscular tetanus neurotoxin reverses muscle atrophy: a randomized controlled trial in dogs with spinal cord injury. Issue 1 (27th October 2021) - Kutschenko, Anna; Manig, Anja; Mönnich, Angelika; Bryl, Beatrice; Alexander, Cécile‐Simone; Deutschland, Martin; Hesse, Stefan; Liebetanz, David
Abstract: Background: Motor symptoms of spinal cord injury (SCI) considerably impair quality of life and are associated with a high risk of secondary diseases. So far, no pharmacological treatment is available for these symptoms. Therefore, we conducted a randomized, double‐blinded, placebo‐controlled study in dogs with spontaneous SCI due to disc herniation to test whether a reduction of spinal inhibitory activity by intramuscular injections of tetanus neurotoxin (TeNT) alleviates motor symptoms such as muscle atrophy or gait function. Methods: To this end, 25 dogs were treated with injections of either TeNT or placebo into their paretic hindlimb muscles. Effects of TeNT on muscle thickness were assessed by ultrasound, while effects on gait function were measured using the modified functional scoring system in dogs. Results: Four weeks after the TeNT injections, muscle thickness of the gluteus medius muscle (before median 1.56 cm [inter‐quartile range IQR 1.34–1.71 cm] and after median 1.56 cm [IQR 1.37–1.85 cm], P ‐value 0.0133) as well as of the rectus femoris muscle (before median 0.76 cm [IQR 0.60–0.98 cm] and after median 0.93 cm [IQR 0.65–1.05 cm], P ‐value 0.0033) significantly increased in the TeNT group. However, there was no difference in gait function between the TeNT and placebo groups. The treatment was well tolerated by all dogs without any signs of generalized tetanus symptoms or any spreading of effects beyond the lumbar level of the injected hindlimbs. Conclusions: With regard to the beneficial effects on muscle thickness, intramuscular injections of TeNT represent the first pharmacological approach that focally reverses muscle atrophy in SCI. Moreover, the study data support the safety of this treatment when TeNT is used at low dose.